Relevance of reforming water legislation under current conditions of Kazakhstan's development - Orazaliev, K.U.; Nurekeshov, T.K.; Rakhymbekova, A.M. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The scientific article presents a review of the country's current legislation regulating water resources management activities, assesses the current situation, and discusses the relevance of reforming water legislation at the current stage of Kazakhstan's development. The authors of the article suggest that new approaches are required to address the issues of legal regulation of relations in the field of water resources use and protection. This necessity is connected, first of all, with the growth of threats coming from new challenges under conditions of ecological and economic problems in the country. The purpose of the scientific article is to review the current legislation of the country regulating water resources management activities, assess the current situation, and analyze the actions and opportunities for reforming water legislation at the current stage of Kazakhstan's development. With the establishment of the new ministry, normative documents necessary for the sector were developed, projects to increase water resources began to be implemented, and measures were taken to develop international cooperation. However, according to the authors, the possibilities of the current legislation, both at the national level and at the level of interstate contractual-legal relations, do not fully take into account the emerging new challenges, so they require further improvement. The authors conclude that the adoption of a new code regulating the industry, revision of strategic documents and new approaches of the state policy in the development of the industry are a necessity and relevant for today.